2007
DOI: 10.1111/j.1741-2358.2007.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of awareness on the outcome of oral health performed by home care service providers

Abstract: The results suggested a high oral care awareness amongst caregiver managers and an inadequate oral care training system. To improve oral health of the dependent elderly, theoretical teaching alone is not sufficient when providing oral health education and a positive contact with the dental team, especially dental hygienists, is an important factor which supports oral care provided by caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…An evaluation of the results of this pilot study showed that the majority of caregivers had received some form of training in oral health care. This is similar to a study of home care service providers 8 where 76.5% had received training in oral care, as well as to another study 3 that reported 57% of managers and 49% of nurses had received oral training. Contrary to these findings, some studies of nurses' aides 7,11,13 have shown that providers were not being adequately didactically or practically trained to provide oral hygiene for individuals with physical and mental disabilities, and they reported many challenges when attempting oral health care.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…An evaluation of the results of this pilot study showed that the majority of caregivers had received some form of training in oral health care. This is similar to a study of home care service providers 8 where 76.5% had received training in oral care, as well as to another study 3 that reported 57% of managers and 49% of nurses had received oral training. Contrary to these findings, some studies of nurses' aides 7,11,13 have shown that providers were not being adequately didactically or practically trained to provide oral hygiene for individuals with physical and mental disabilities, and they reported many challenges when attempting oral health care.…”
Section: Discussionsupporting
confidence: 88%
“…The current literature lacks information on perceived comfort, behaviors, and barriers encountered by group home staff members who provide daily oral care for individuals with SHCN. There is substantial research with regard to the elderly populations treated in long‐term care facilities, 3 , 7–16 but very little on younger populations. Many of the same perceptions, behaviors, and barriers experienced by nurses’ aides can be paralleled to the caregivers who work with the population of SHCN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, an evaluation of the bivariate analysis showed that being trained at one's current facility, as well as having had previous oral care training, was significant. In a similar study of home care service providers, 76.5% had received training in oral care, while in another study, 57% of managers and 49% of nurses had received training. Other studies of nurses’ aides have shown that providers who were not adequately trained to provide oral hygiene for consumers with SHCN reported many challenges when attempting to provide oral health care.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is abundant research regarding elderly populations who live in long-term facilities. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] In their study regarding oral care delivery for nursing facility residents, Chalmers et al 7 indicated that 80% of nurses' aides reported residents not opening their mouths, biting the toothbrush, and refusing oral care. Other difficulties included kicking, hitting, spitting, and biting the nurses' aide.…”
Section: A R T I C L Ementioning
confidence: 99%